Norovirus P particle efficiently elicits innate, humoral and cellular immunity. - Hao Fang (Public Library of Science (PLoS), 2013)
Norovirus (NoV) P domain complexes, the 24 mer P particles and the P dimers, induced effective humoral immunity, but their role in the cellular immune responses remained unclear. We reported here a study on cellular immune responses of the two P domain complexes in comparison with the virus-like particle (VLP) of a GII.4 NoV (VA387) in mice. The P domain complexes induced significant central memory CD4(+) T cell phenotypes (CD4(+) CD44(+) CD62L(+) CCR7(+)) and activated polyclonal CD4(+) T cells as shown by production of Interleukin (IL)-2, Interferon (IFN)-γ, and Tumor Necrosis Factor (TNF)-α. Most importantly, VA387-specific CD4(+) T cell epitope induced a production of IFN-γ, indicating an antigen-specific CD4(+) T cell response in P domain complex-immunized mice. Furthermore, P domain complexes efficiently induced bone marrow-derived dendritic cell (BMDC) maturation, evidenced by up-regulation of co-stimulatory and MHC class II molecules, as well as production of IL-12 and IL-1β. Finally, P domain complex-induced mature dendritic cells (DCs) elicited proliferation of specific CD4(+) T cells targeting VA387 P domain. Overall, we conclude that the NoV P domain complexes are efficiently presented by DCs to elicit not only humoral but also cellular immune responses against NoVs. Since the P particle is highly effective for both humoral and cellular immune responses and easily produced in Escherichia coli (E. coli), it is a good choice of vaccine against NoVs and a vaccine platform against other diseases.